Development of Magnetic-Silica Particles and In-house Buffers Kit for SARS-CoV-2 and CDV RNA Extraction - Ahadi Damar Prasetya; Muflikhah Muflikhah; Wildan Zakiah Lubis; Andon Insani; Grace Tjungirai Sulungbudi; Mujamilah Mujamilah; Uus Saepulloh (Universitas Gadjah Mada, 2024)
Since the end of 2019, COVID-19 pandemic caused by the novel SARS-CoV-2 has become a serious problem for the world. Accurate and rapid techniques in testing and tracing are needed to control the virus spreading. Molecular diagnostics through gene amplification techniques, especially PCR, still become the gold standard for SARS-CoV-2 detection, which requires the first step of RNA extraction and purification. The limitations of commercial RNA extraction-purification kits during the pandemic caused a big problem in testing and tracing, especially for developing countries. A simple RNA extraction-purification kit based on magnetic-silica (MAGSi) beads and non-guanidine in-house buffers for RNA virus extraction-purification has been developed. Two types of MAGSi beads with different magnetic nanoparticles (MNPs) content were synthesized through a modified Stöber’s method using the sonication technique. The PCR result shows that both the MAGSi beads and the buffer can be used as a kit for RNA extraction-purification, tested for SARS-CoV-2 and Canine Distemper Virus. Further study shows that MAGSi-1 has better RNA extraction ability, and a higher concentration of RNA has been extracted. This is likely because of the smaller particle size distribution (50–1,500 nm distribution) and higher magnetization (20.2 emu/g) of MAGSi-1 compared to MAGSi-2 with 100–1,700 nm size distribution and 14.2 emu/g magnetization.